Michael Dukakis Rally at Fresno Amtrak Station - Watkins, Howard::::::::: (1988)
Michael Dukakis speaking on dais; others include: ?, U.S. Senator Alan Cranston, ?, Juan Arambula, ?, Les Kimber, Gary Condit, Assemblymember Bruce Bronzan, Congressman Richard Lehman, Mary Bronzan, and Chloe Bronzan